The deterrent effect of the SEC Whistleblower Program on financial reporting securities violations - Wiedman, Christine; Zhu, Chunmei (Contemporary Accounting Research, 2023)
Abstract The stated goal of the SEC Whistleblower Program introduced as part of the Dodd‐Frank Act was to deter securities violations and thereby to strengthen investor protection. We document significant reductions in the likelihood of financial reporting fraud by US firms following the introduction of this program. The reductions are robust to controlling for other regulatory changes in the Dodd‐Frank Act and economic trends. Given that employees of firms with weaker internal compliance and reporting programs are more likely to report irregularities directly to the SEC rather than internally, we predict and find that these firms are more likely to change their reporting behavior. We also show that the observed reductions are attributable to an improvement in internal whistleblower programs and the hiring of more capable audit committee members after the program's inception. Collectively, these findings provide important large‐sample evidence of significant benefits of the SEC Whistleblower Program for deterring financial reporting fraud and of the efficacy of bounty‐type whistleblower programs.